Lentinan Attenuates Damage of the Small Intestinal Mucosa, Liver, and Lung in Mice with Gut-Origin Sepsis - Zhongshen Kuang; Tingting Jin; ChangYi Wu; Yanan Zong; Panpan Yin; WangYu Dong; Xue Lin; WeiYan You; Chenlong Zhang; Lijie Wang; Yongying Liu; Shan Ren; et al. (Journal of Immunology Research)
This study is aimed at exploring the effects of lentinan on small intestinal mucosa as well as lung and liver injury in mice with gut-origin sepsis. Cecal ligation and perforation (CLP) were used to construct a mouse model of gut-origin sepsis. The mice were randomly divided into six groups: sham operation group (sham), gut-origin sepsis model group (CLP), ulinastatin-positive drug control group (UTI), lentinan low concentration group (LTN-L, 5 mg/kg), lentinan medium concentration group (LTN-M, 10 mg/kg), and lentinan high concentration group (LTN-H, 20 mg/kg). H&E staining was used to detect the pathological damage of the small intestine, liver, and lung. The serum of mice in each group was collected to detect the expression changes of inflammatory cytokines, oxidative stress biomarkers, and liver function indexes. In vitro assessment of bacterial translocation was achieved through inoculated culture media. Western blot and RT-qPCR were used to detect the expression of molecules related to the NF-κB signaling pathway in the small intestine tissues of mice. The results showed that compared with the CLP group, the injury degree of the small intestine, liver, and lung in mice with gut-origin sepsis was improved with the increase of lentinan concentration. In addition, TNF-α, IL-1β, IL-6, and HMGB1 were decreased with the increase of lentinan concentration, but the expression of IL-10 was increased. Lentinan could also reduce the expression of oxidative stress injury indexes and liver function indexes and inhibit bacterial translocation to liver and lung tissues. Further mechanism investigation revealed that lentinan downregulated the expression of the NF-κB signaling pathway molecules (NF-κB, TLR4, and Bax) and upregulated the expression of occludin and Bcl-2. In conclusion, lentinan inhibits the activity of the NF-κB signaling pathway, thus attenuating injuries of small intestinal mucosa and liver and lung in mice with gut-origin sepsis and reducing the inflammatory response in the process of sepsis.